Using real world data to bridge the evidence gap left by prostate cancer screening trials - N. Norori; N. Burns-Cox; L. Blaney; N. Mayor; A. Rylance; T.T. Shah; A. Naranjo; M.D. Hobbs (ESMO Real World Data and Digital Oncology)
Background and purpose: Population-based prostate cancer screening is currently not recommended in the UK because harms may outweigh benefits. Recent changes to the diagnostic pathway have improved safety and accuracy, but uncertainty remains as to how much they have shifted the screening harm to benefit ratio. Our work uses modelling and real-world data (RWD) to bridge this evidence gap. Materials and methods: We analysed outcomes of men entering the current prostate cancer diagnostic pathway using RWD from two NHS registries covering 16 hospitals. To assess improvements, we compared current UK clinical practice outcomes with those reported in the Cluster Randomised Trial of PSA Testing for Prostate Cancer (CAP)/ProtecT trial and past UK clinical practice, and to a model built to represent expected outcomes from the UK current diagnostic pathway. Results: Out of 10 000 men who underwent a prostate specific antigen (PSA) test, we estimated that the proportion of men with no cancer after a biopsy following a PSA test decreased from 9.46% in the pre-magnetic resonance imaging CAP/ProtecT pathway to 2.33% and 1.52% in the Rapid Assessment for Prostate Imaging and Diagnosis (RAPID) and South West of England RWD pathways, respectively. Clinically insignificant prostate cancer diagnoses decreased to 0.73% in RAPID and 0.83% in South West, while the proportion of men experiencing sepsis reduced from a historic 0.10% to 0.02% in RAPID. We estimated an increase in clinically significant prostate cancer diagnoses in the RWD pathways. Conclusions: This analysis of high-quality RWD estimates a 79% decrease in harm from the diagnostic process when comparing the previous pathway to actual outcomes from current UK clinical practice. This confirms and quantifies the harm reduction delivered by new diagnostic techniques.